Method for producing rare earth magnet, and rare earth magnet

By adjusting the pressure and temperature conditions of pressurized sintering during the manufacturing process of rare earth magnets, the problem of excessive reaction between magnetic corresponding change and zinc components in the prior art is solved, and the high density and magnetic characteristics of rare earth magnets are achieved.

CN119811879APending Publication Date: 2025-04-11TOYOTA JIDOSHA KK +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411407715.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-11
Filing Date
2024-10-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing rare earth magnet manufacturing method causes strain accumulation of magnetic phase and excessive reaction of zinc components under high pressure and high temperature pressurized sintering conditions, thereby reducing the residual magnetization strength.

Method used

Pressurized sintering of the magnetic field molded body at a pressure of 500 MPa or more and 900 MPa or less and a temperature of 360°C or more and 390°C or less, and a sintering time of 1 hour or more and 24 hours or less is controlled to achieve high density of the sintered body and strain suppression of the magnetic phase.

Benefits of technology

The magnetic properties of rare earth magnets are improved, including residual magnetization, and the performance of magnets is enhanced by increasing density and suppressing the strain of the magnetic phase.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119811879A_ABST
    Figure CN119811879A_ABST
Patent Text Reader

Abstract

The invention relates to a method for manufacturing a rare earth magnet and a rare earth magnet. Provided is a method for producing a rare earth magnet, whereby magnetic characteristics can be improved by increasing the density of a sintered body and suppressing the strain of a magnetic phase. This method for producing a rare earth magnet is characterized by comprising: a step for preparing a magnetic powder containing Sm, Fe, and N; a step for preparing a modifying material powder containing at least one of metal zinc and a zinc alloy; a step for obtaining a mixed powder by mixing the magnetic powder and the modifying material powder; a step for obtaining a magnetic field molded body by compression molding the mixed powder in a magnetic field; and a step for obtaining a sintered body by pressure sintering the magnetic field molded body, in which the magnetic field molded body is pressure-sintered at a pressure of 500 MPa to 900 MPa (inclusive) and a temperature of 360 DEG C to 390 DEG C (inclusive) for a time of 1 hour to 24 hours (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a rare earth magnet and a rare earth magnet, and more particularly to a method for producing a rare earth magnet formed by sintering magnetic powder containing Sm, Fe and N and a rare earth magnet. Background Art

[0002] In the past, SmCo-based rare earth magnets and NdFeB-based rare earth magnets have been put into practical use as high-performance rare earth magnets, but in recent years, SmFeN-based rare earth magnets containing Sm, Fe and N have been developed as rare earth magnets other than these. SmFeN-based rare earth magnets are manufactured using SmFeN-based magnetic powders containing Sm, Fe and N. As a manufacturing method of SmFeN-based rare earth magnets and rare earth magnets, for example, the following manufacturing method of rare earth magnets and rare earth magnets obtained by the manufacturing method are known, and the manufacturing method includes: mixing SmFeN-based magnetic powders and modified material powders containing zinc components to obtain a mixed powder; compressing the mixed powder in a magnetic field to obtain a magnetic field molded body; and pressure sintering the magnetic field molded body to obtain a sintered body (Patent Document 1).

[0003] Prior Art Literature

[0004] Patent Document 1: Japanese Patent Application Publication No. 2023-077289 Summary of the invention

[0005] In the method for manufacturing a rare earth magnet described in Patent Document 1, demagnetization is suppressed by reacting the zinc components of the SmFeN-based magnetic powder and the modified material powder during pressure sintering to form a modified phase on the surface of the magnetic powder. In addition, in order to increase the density of the sintered body for the purpose of improving the magnetic properties, the magnetic field forming body is pressure-sintered for more than 1 minute and less than 30 minutes at a pressure of more than 200 MPa and less than 1500 MPa and a temperature of more than 300°C and less than 400°C during pressure sintering. However, under such conventional pressure sintering conditions, due to the high pressure, strain accumulates in the magnetic phase of the sintered body, resulting in the inability to increase the residual magnetization. In addition, due to the high temperature, the zinc components of the SmFeN-based magnetic powder and the modified material powder react excessively, which may reduce the proportion of the magnetic phase in the sintered body, and the residual magnetization may be reduced.

[0006] The present invention has been made in view of the above problems, and an object of the present invention is to provide a method for producing a rare earth magnet and a rare earth magnet capable of improving magnetic properties by increasing the density of a sintered body and suppressing strain in a magnetic phase.

[0007] In order to solve the above-mentioned problems, the manufacturing method of the rare earth magnet of the present invention is characterized in that it comprises: a step of preparing a magnetic powder containing Sm, Fe and N (magnetic powder preparation step); a step of preparing a modified material powder containing at least one of metallic zinc and a zinc alloy (modified material powder preparation step); a step of obtaining a mixed powder by mixing the above-mentioned magnetic powder and the above-mentioned modified material powder (mixing step); a step of obtaining a magnetic field formed body by compression molding the above-mentioned mixed powder in a magnetic field (magnetic field molding step); and a step of obtaining a sintered body by pressure sintering the above-mentioned magnetic field formed body (pressure sintering step), in which the above-mentioned pressure sintering is performed at a pressure of not less than 500 MPa and not more than 900 MPa and a temperature of not less than 360°C and not more than 390°C for a time of not less than 1 hour and not more than 24 hours.

[0008] In addition, in order to solve the above-mentioned problems, the rare earth magnet of the present invention is characterized in that it comprises a sintered body of a mixed powder, wherein the mixed powder comprises a magnetic powder and a modifying material powder, wherein the magnetic powder contains Sm, Fe and N, and the modifying material powder contains at least one of metallic zinc and a zinc alloy, and the half-value width of the diffraction peak of the (024) plane measured by X-ray diffraction of the sintered body is less than 0.2 degrees, and the bulk density of the sintered body is 6.2 g / cm 3 above.

[0009] According to the present invention, the magnetic properties can be improved by increasing the density of the sintered body and suppressing the strain of the magnetic phase. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 (a) to (d) are schematic process diagrams showing a method for producing a rare earth magnet according to one embodiment.

[0011] Figure 2 (a) and (b) are schematic process diagrams showing a method for producing a rare earth magnet according to one embodiment.

[0012] Description of Reference Numerals

[0013] 1: Rare earth magnet, 2: Coated magnetic particles, 2a: Magnetic particles, 2b: Phosphoric acid coating, 4: Coated magnetic powder, 5: Modified phase, 6: Metal zinc particles, 8: Metal zinc powder (modified material powder), 10A: Mixed powder, 10B: Magnetic field formed body, 10C: Sintered body DETAILED DESCRIPTION

[0014] First, a method for producing a rare earth magnet according to an embodiment and an outline of the rare earth magnet will be described by taking one embodiment as an example. Figure 1 (a)~ Figure 2(b) is a schematic process diagram showing a method for producing a rare earth magnet according to one embodiment.

[0015] In a method for producing a rare earth magnet according to one embodiment, first, Figure 1 As shown in (a), a coated magnetic powder 4 is prepared (magnetic powder preparation step). The coated magnetic powder 4 includes coated magnetic particles 2, wherein the coated magnetic particles 2 have: magnetic particles 2a having a magnetic phase, and a phosphate coating 2b covering the surface of the magnetic particles 2a. The coated magnetic powder 4 is an anisotropic magnetic powder. The magnetic particles 2a contain Sm, Fe, and N. Next, as Figure 1 As shown in (b), as the modifying material powder 8, a metal zinc powder 8 containing metal zinc particles 6 is prepared (modifying material powder preparation step). Figure 1 As shown in (c), the coated magnetic powder 4 and the metal zinc powder 8 are mixed to obtain a mixed powder 10A (mixing step).

[0016] Then, if Figure 1 As shown in (d), by using a molding metal mold 40 and an electromagnetic coil 50, the mixed powder 10A is compression molded in a magnetic field (magnetic field molding) to obtain a magnetic field molded body 10B (magnetic field molding process). The molding metal mold 40 includes a die 40A and a punch 40B, the die 40A has a cavity 40C, and the punch 40B slides inside the cavity 40C. The electromagnetic coil 50 is arranged on both sides around the die 40A in a direction perpendicular to the sliding direction of the punch 40B (the direction of the hollow arrow). The magnetic field molding is performed in a nitrogen atmosphere. At this time, first, the mixed powder 10A is accommodated in the cavity 40C of the die 40A in a nitrogen atmosphere. Next, the mixed powder 10A is compression molded by applying a magnetic field in a direction perpendicular to the sliding direction of the punch 40B (the direction of the arrow) to the mixed powder 10A in the cavity 40C of the die 40A using the electromagnetic coil 50 while moving the punch 40B.

[0017] Then, if Figure 2As shown in (a), the magnetic field forming body 10B is pressure-sintered using a sintering metal mold 60 and a heating heater 70 to obtain a sintered body 10C (pressure sintering step). The sintering metal mold 60 includes a die 60A and a punch 60B, the die 60A has a cavity 60C, and the punch 60B slides inside the cavity 60C. The heating heater 70 includes a high-frequency induction coil 70A arranged around the die 60A in a direction perpendicular to the sliding direction of the punch 60B (the direction of the hollow arrow). The pressure sintering is performed in an argon atmosphere. At this time, first, the magnetic field forming body 10B is moved from the die 40A of the forming metal mold 40 to the cavity 60C of the die 60A of the sintering metal mold 60. Next, the magnetic field forming body 10B is pressurized by moving the punch 60B while heating the magnetic field forming body 10B in the cavity 60C of the die 60A using the high-frequency induction coil 70A. In this way, the magnetic field forming body 10B is pressure-sintered at a pressure of 500 MPa to 900 MPa and a temperature of 360° C. to 390° C. for a period of time of 1 hour to 24 hours.

[0018] Next, although not shown, the punch 60B of the sintering die 60 is moved to remove the sintered body 10C from the cavity 60C of the die 60A. Figure 2 As shown in (b), as a rare earth magnet involved in one embodiment, a rare earth magnet 1 having a sintered body 10C is manufactured. In the rare earth magnet 1, in the sintered body 10C, the magnetic particles 2a are bonded by the modified phase 5 formed by alloying the α-Fe phase on the surface thereof with the zinc component of the modified material powder 8. Moreover, in the X-ray diffraction pattern measured by X-ray diffraction of the surface of the sintered body 10C, the half-value width of the diffraction peak of the (024) plane of the crystal structure of the magnetic phase of the magnetic particles 2a of the sintered body 10C is less than 0.2 degrees. Moreover, the bulk density of the sintered body 10C is 6.2 g / cm 3 above.

[0019] In the method for manufacturing a rare earth magnet according to one embodiment, in the pressure sintering step, the magnetic field forming body is pressure sintered for a period of time of 1 hour to 24 hours at a pressure of 500 MPa to 900 MPa and a temperature of 360°C to 390°C. By performing pressure sintering under conditions of lower pressure and longer time than conventional conditions, the bulk density of the sintered body can be made to be 6.2 g / cm 3The above, and the half-value width of the diffraction peak of the (024) plane of the crystal structure of the magnetic phase of the magnetic particles of the sintered body can be made less than 0.2 degrees. That is, the high density of the sintered body of the rare earth magnet involved in one embodiment and the suppression of the strain of the magnetic phase can be achieved at the same time. As a result, the magnetic properties such as the residual magnetization intensity of the rare earth magnet involved in one embodiment can be improved. Next, the manufacturing method of the rare earth magnet involved in the embodiment and the details of the rare earth magnet are described.

[0020] 1. Manufacturing method of rare earth magnets

[0021] The method for producing a rare earth magnet comprises: a magnetic powder preparation step, a modified material powder preparation step, a mixing step, a magnetic field forming step and a pressure sintering step.

[0022] (1) Magnetic powder preparation process

[0023] In the magnetic powder preparation step, a magnetic powder containing Sm, Fe and N (hereinafter sometimes referred to as "SmFeN-based magnetic powder" or "magnetic powder") is prepared. As the SmFeN-based magnetic powder, there is no particular limitation as long as it is a magnetic powder containing magnetic particles having a magnetic phase and containing Sm, Fe and N. The SmFeN-based magnetic powder may be a general magnetic powder, but is usually an anisotropic magnetic powder. As the SmFeN-based magnetic powder, for example, it may be an uncoated magnetic powder in which the surface of the magnetic particles is not covered with a phosphate coating, or it may be a coated magnetic powder containing coated magnetic particles, wherein the coated magnetic particles have magnetic particles and a phosphate coating covering the surface of the magnetic particles. As the SmFeN-based magnetic powder, a coated magnetic powder is preferred. This is because the phosphate coating can suppress the degradation caused by oxidation of the magnetic particles in the manufacturing process of the magnet.

[0024] The magnetic phase of the magnetic particles of the magnetic powder is not particularly limited as long as it contains Sm, Fe and N. It can be a general magnetic phase or a phase having at least a portion of Th2Zn 17 Type and Th2Ni 17 The magnetic phase is not particularly limited, and further examples thereof include a phase having a TbCu7 type crystal structure. Furthermore, Sm is samarium, Fe is iron, and N is nitrogen. In addition, Th is thorium, Zn is zinc, Ni is nickel, Tb is terbium, and Cu is copper. Rare earth magnets embody magnetization by the magnetic phase of magnetic particles derived from magnetic powder.

[0025] The magnetic particles used as magnetic powder are not particularly limited as long as they have a magnetic phase as described above and contain Sm, Fe and N. They may have a general composition. For example, particles containing at least one element selected from La, W and R (R is at least one selected from Ti, Ba, Sr and Co) in addition to Sm, Fe and N can be mentioned. Among them, particles whose composition is preferably represented by the following general formula (1).

[0026] Sm v Fe (100-v-w-x-y-z) N w La x W y R z (1)

[0027] (In the formula, the subscripts v, w, x, y and z satisfy the conditions of 3≤v≤30, 3≤w≤15, 0≤x≤0.5, 0≤y≤2.5 and 0≤z≤0.3).

[0028] In the above general formula (1), v is set to be 3 or more and 30 or less because: when v is less than 3, the unreacted part of the iron component (α-Fe phase) separates and the coercivity of the magnetic powder may decrease; when v exceeds 30, the Sm element precipitates, the magnetic powder becomes unstable in the atmosphere, and the residual magnetization may decrease. w is set to be 3 or more and 15 or less because: when w is less than 3, the coercivity can hardly be manifested; when w exceeds 15, Sm and / or nitrides of iron itself may be generated. x is 0 or more and 0.5 or less, but preferably 0.05 or more and 0.5 or less. When x is less than 0.05, the effect of addition is insufficient; when x exceeds 0.5, Sm and / or nitrides of iron itself may be generated, thereby reducing the magnetization. y is 0 or more and 2.5 or less, but preferably 0.05 or more and 2.5 or less. When y is less than 0.05, the effect of addition is insufficient. When y exceeds 2.5, Sm and / or nitrides of iron itself may be generated, thereby reducing the magnetization. z is greater than 0 and less than 0.3, but preferably greater than 0.0001 and less than 0.3. When z is less than 0.0001, the effect of addition is insufficient, and Sm and / or nitrides of iron itself may be generated, thereby reducing the magnetization.

[0029] The content of Sm in the magnetic particles of the magnetic powder is, for example, preferably from 3 mass % to 30 mass %, particularly preferably from 20 mass % to 25 mass %. The content of N in the magnetic particles of the magnetic powder is, for example, preferably from 3 mass % to 15 mass %, particularly preferably from 3.3 mass % to 3.5 mass %. When the content of N is too much, excessive nitridation occurs; when the content of N is too little, insufficient nitridation occurs, and there is a tendency for the magnetic properties to decrease. Furthermore, the content of Fe in the magnetic particles of the magnetic powder is the amount obtained by removing the content of elements other than Fe from the content of all elements contained in the magnetic particles of the magnetic powder.

[0030] When the magnetic particles of the magnetic powder further contain La, for example, from the viewpoint of residual magnetization, the content of La is preferably 0.1 mass % or more and 5 mass % or less, and particularly preferably 0.15 mass % or more and 1 mass % or less. When the magnetic particles of the magnetic powder further contain W, for example, from the viewpoint of coercive force, the content of W is preferably 0.1 mass % or more and 5 mass % or less, and particularly preferably 0.15 mass % or more and 1 mass % or less. When the magnetic particles of the magnetic powder further contain R, for example, from the viewpoint of temperature characteristics, the content of R is preferably 1.0 mass % or less, and particularly preferably 0.5 mass % or less.

[0031] Cumulative 50% particle size D in the volume-based particle size distribution of the magnetic powder 50 The median diameter is not particularly limited and may be a general median diameter. However, in the case of coated magnetic powder, the median diameter is preferably 2 μm or more and 5 μm or less, and particularly preferably 2.5 μm or more and 4.5 μm or less. 50 If the D of the magnetic powder is too small, the amount of magnetic powder in the magnet will be reduced, and the magnetization strength may be reduced. 50 If the value is too large, the coercive force of the magnet tends to decrease. 50 The same is true for the magnetic powder D when the magnetic powder is a coated magnetic powder. 50 Similarly. Furthermore, the D of magnetic powder 50 For example, it can be determined by measuring using a laser diffraction particle size distribution measuring device or the like.

[0032] The coated magnetic powder is obtained by subjecting a magnetic powder containing magnetic particles to phosphoric acid treatment, wherein the magnetic particles have a magnetic phase containing Sm, Fe and N. By subjecting the magnetic powder to phosphoric acid treatment, a phosphoric acid coating as a passive film having PO bonds is formed on the surface of the magnetic particles of the magnetic powder. In the phosphoric acid treatment, the magnetic powder is reacted with a phosphoric acid treatment agent such as a phosphate such as orthophosphoric acid. At this time, a method of adding the magnetic powder to a phosphoric acid solution, which is obtained by dissolving the phosphoric acid treatment agent in water, an organic solvent, etc., can be used. Furthermore, in the case of subjecting the magnetic powder to phosphoric acid treatment, it is preferred to dry the magnetic powder under normal pressure or under vacuum after the phosphoric acid treatment. This is because the coercive force of the magnet can be increased by chemically bonding the phosphoric acid coating to the magnetic particles. Furthermore, the drying temperature is preferably above 140°C. The thickness of the phosphoric acid coating is not particularly limited and can be a general thickness. The thickness of the phosphoric acid coating is, for example, greater than 1 nm and less than 50 nm, preferably greater than 5 nm and less than 30 nm.

[0033] (2) Modified material powder preparation process

[0034] In the modifying material powder preparation step, modifying material powder containing at least one of metallic zinc and zinc alloy is prepared. The modifying material powder modifies and bonds magnetic particles of the magnetic powder with a zinc component.

[0035] The modifying material powder is not particularly limited as long as it is the above-mentioned powder, and may be a general modifying material powder. The modifying material powder may be, for example, a metal zinc powder containing metal zinc particles or a zinc alloy powder containing zinc alloy particles.

[0036] Zinc alloy is Zn with other elements (M 2 ) alloyed (hereinafter sometimes referred to as "Zn-M 2 "). Here, Zn is zinc, M 2 It is an element other than zinc. 2 There is no particular limitation as long as it is an element that can be alloyed with Zn, and it may be a common element. 2 For example, it is preferred to include one or more elements selected from elements that lower the melting start temperature of the zinc alloy compared to the melting point of Zn (hereinafter sometimes referred to as "melting point lowering elements") and inevitable impurity elements. This is because the sintering property during pressure sintering is improved. As the melting point lowering element, for example, there can be mentioned elements that can form a eutectic alloy with Zn, and specifically, there can be mentioned one or more elements such as Sn, Mg, and Al. Sn is tin, Mg is magnesium, and Al is aluminum. Furthermore, as M 2In addition to the melting point lowering elements and inevitable impurity elements, the magnet may further contain one or more elements that do not impair the melting point lowering effect of the melting point lowering elements and the properties of the magnet. The so-called inevitable impurity elements include impurity elements that cannot be avoided in the modified material powder, such as impurities contained in the raw materials of the modified material powder, and impurity elements that require significant costs to avoid being contained in the modified material powder. Zn-M 2 Zn and M 2 The molar ratio of Zn-M is not particularly limited and may be a general molar ratio as long as it is appropriately determined so that the sintering temperature during pressure sintering becomes appropriate. 2 M 2 The molar ratio of Zn-M is, for example, 0.05 or more, preferably 0.10 or more, and particularly preferably 0.20 or more. 2 M 2 The molar ratio is, for example, 0.90 or less, preferably 0.80 or less, particularly preferably 0.70 or less, 0.60 or less, 0.50 or less, 0.40 or less, or 0.30 or less.

[0037] The total content of metallic zinc and zinc alloy in the modified material powder is not particularly limited, and may be a general content, for example, 90% by mass or more and 100% by mass or less, preferably 95% by mass or more and 100% by mass or less. The modified material powder may contain, in addition to metallic zinc and zinc alloy, any substance having at least one of bonding function, modification function and other functions (such as function of improving corrosion resistance) within the limit that does not impair the effect of the present invention. The content of such a substance in the modified material powder is, for example, the content of the portion after removing metallic zinc and zinc alloy from the total modified material powder.

[0038] Cumulative 50% particle size D in the volume-based particle size distribution of the modified material powder 50 (Median diameter) is not particularly limited, but is, for example, 0.1 μm or more, preferably 0.5 μm or more, and particularly preferably 1 μm or more. 50 For example, it is 4 μm or less, preferably 2 μm or less, and particularly preferably 1 μm or less. 50 For example, it can be determined by measuring using a laser diffraction particle size distribution measuring device or the like.

[0039] (3) Mixing process

[0040] In the mixing step, the magnetic powder and the modifier powder are mixed to obtain a mixed powder. The content of the modifier powder in the mixed powder is not particularly limited and may be a general content, but from the viewpoint of residual magnetization, for example, it is preferably 2 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the SmFeN-based magnetic powder, and particularly preferably 5 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the SmFeN-based magnetic powder.

[0041] The method for mixing the magnetic powder and the modifying material powder is not particularly limited and may be a common method, for example, a mortar, a roller mixer, a stirring mixer, a mechanofusion machine, a V-type mixer, a ball mill, etc.

[0042] (4) Magnetic Field Forming Process

[0043] In the magnetic field forming step, the mixed powder is compressed and formed in a magnetic field (hereinafter sometimes referred to as "magnetic field forming") to obtain a magnetic field formed body. Orientation is imparted to the magnetic field formed body. As a result, anisotropy is imparted to the rare earth magnet, and the residual magnetization strength is improved.

[0044] The method of magnetic field molding is not particularly limited, and it can be a general method, for example, a method in which a magnetic field is applied to the mixed powder by a magnetic field generating device arranged around a molding die such as a metal mold, and the mixed powder is compressed and molded by a molding die. As a magnetic field generating device, for example, a device such as an electromagnetic coil that applies a static magnetic field, a device that uses an alternating current to apply a pulsed magnetic field, etc. can be cited. The atmosphere for magnetic field molding is not particularly limited, but for example, an inert gas atmosphere such as an argon atmosphere and a nitrogen atmosphere is preferred. This is because the oxidation of the magnetic field molded body can be suppressed. The molding pressure of the magnetic field molding is, for example, more than 10MPa, preferably more than 20MPa, and particularly preferably more than 30MPa, more than 50MPa, and more than 100MPa. The molding pressure is, for example, less than 1500MPa, preferably less than 1000MPa, and particularly preferably less than 500MPa, less than 200MPa, and less than 100MPa. The application time of the molding pressure is, for example, more than 0.5 minutes, preferably more than 1 minute, and particularly preferably more than 3 minutes. The application time of the molding pressure is, for example, 10 minutes or less, preferably 7 minutes or less, and particularly preferably 5 minutes or less. The magnitude of the magnetic field in the magnetic field molding is, for example, 500 kA / m or more, preferably 1000 kA / m or more, particularly preferably 1500 kA / m or more, 1600 kA / m or more. The magnitude of the magnetic field is, for example, 20000 kA / m or less, preferably 15000 kA / m or less, particularly preferably 10000 kA / m or less, 5000 kA / m or less, 3000 kA / m or less, 2000 kA / m or less.

[0045] (5) Pressure sintering process

[0046] In the pressure sintering step, a sintered body is obtained by pressure sintering the magnetic field formed body (hereinafter sometimes referred to as "pressure sintering"). The method of pressure sintering is not particularly limited, and it can be a general method, for example, a method of pressurizing the magnetic field formed body with a forming die such as a metal mold while heating the magnetic field formed body with a heating device. As a heating device, for example, a heating heater having a high-frequency induction coil arranged around the forming die can be mentioned. The atmosphere for pressure sintering is not particularly limited, and for example, an inert gas atmosphere such as an argon atmosphere and a nitrogen atmosphere is preferably used. This is because the oxidation of the sintered body can be suppressed.

[0047] In the pressure sintering, the magnetic field molded body is pressure sintered at a pressure of 500 MPa to 900 MPa and a temperature of 360°C to 390°C for 1 hour to 24 hours. This can simultaneously achieve high density of the sintered body of the rare earth magnet and suppression of strain in the magnetic phase.

[0048] When the pressure of pressure sintering is 500MPa or more and 900MPa or less, the high density of the sintered body and the suppression of the strain of the magnetic phase can be achieved. When the temperature of pressure sintering is 360°C or more and 390°C or less, the following modified phase can be formed, which can suppress demagnetization. The modified phase is an Fe-Zn alloy phase obtained by alloying the α-Fe phase of the surface part of the magnetic particles with the zinc component of the modified material powder located on the surface of the magnetic particles. In addition, the high density of the sintered body and the suppression of the strain of the magnetic phase can be achieved. When the temperature is less than 360°C, the modified phase may not be formed. When the temperature exceeds 390°C, the zinc component of the magnetic powder and the modified material powder reacts excessively, thereby reducing the proportion of the magnetic phase in the sintered body and increasing the strain of the magnetic phase. In addition, various phases such as alloy phases and α-Fe phases of different types from the modified phase are generated on the surface of the magnetic particles, which become the cause of demagnetization. When the time of pressure sintering is 1 hour or more and 24 hours or less, the high density of the sintered body and the suppression of the strain of the magnetic phase can be achieved. When the time is less than 1 hour, there is a possibility that the sintered body cannot be made denser.

[0049] (6) Method for manufacturing rare earth magnets

[0050] The method for manufacturing a rare earth magnet is not particularly limited as long as it is a method having the above steps, but for example, it is preferably: the magnetic powder is a coated magnetic powder comprising coated magnetic particles, the coated magnetic particles have magnetic particles and a phosphate coating covering the surface of the magnetic particles, the magnetic particles have a magnetic phase containing Sm, Fe and N, the modified material powder is a metal zinc powder, and the content of the modified material powder in the mixed powder is 5 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the magnetic powder. This is because it is easy to make the half-value width of the diffraction peak of the (024) plane of the sintered body measured by X-ray diffraction to be less than 0.2 degrees, and the bulk density of the sintered body to be 6.2g / cm 3 That is, this is because it is easy to simultaneously achieve high density of the sintered body of the rare earth magnet and suppression of strain in the magnetic phase. As a method for manufacturing a rare earth magnet, for example, it is preferred that: the cumulative 50% particle size D in the volume-based particle size distribution of the magnetic powder is 50 The cumulative 50% particle size D in the volume-based particle size distribution of the modifying material powder is 2 μm or more and 5 μm or less. 50 The method of making the particle size of the rare earth magnet sintered body higher than or equal to 0.1 μm and less than or equal to 4 μm is because it is easy to simultaneously achieve high density of the sintered body of the rare earth magnet and suppression of strain in the magnetic phase.

[0051] 2. Rare earth magnets

[0052] The rare earth magnet comprises a sintered body of a mixed powder, wherein the mixed powder comprises a magnetic powder and a modifying material powder, wherein the magnetic powder contains Sm, Fe and N, and the modifying material powder contains at least one of metallic zinc and a zinc alloy, wherein the half-value width of a diffraction peak of a (024) plane measured by X-ray diffraction of the sintered body is less than 0.2 degrees, and the bulk density of the sintered body is 6.2 g / cm 3 The rare earth magnet is not particularly limited as long as it is the rare earth magnet described above, but is preferably manufactured by the method for manufacturing a rare earth magnet described in the above “1. Method for manufacturing a rare earth magnet”, for example.

[0053] The magnetic powder contained in the mixed powder used in the sintered body of the rare earth magnet is the same as the SmFeN-based magnetic powder described in the above "1. Method for producing rare earth magnet (1) Magnetic powder preparation step". The modified material powder contained in the mixed powder is the same as the modified material powder described in the above "1. Method for producing rare earth magnet (2) Modified material powder preparation step". The mixed powder is the same as the mixed powder described in the above "1. Method for producing rare earth magnet (3) Mixing step". The sintered body of the rare earth magnet is not particularly limited as long as it is the above-mentioned sintered body, but for example, it is preferably a sintered body of a magnetic field formed body of the mixed powder.

[0054] Example

[0055] Hereinafter, the method for producing the rare earth magnet and the rare earth magnet according to the embodiment will be described in more detail with reference to Examples and Comparative Examples.

[0056] [Example 1]

[0057] An example of a method for manufacturing a rare earth magnet according to one embodiment of the present invention is implemented. First, a coated magnetic powder is prepared (magnetic powder preparation step). The coated magnetic powder includes coated magnetic particles, wherein the coated magnetic particles have magnetic particles having a magnetic phase and a phosphate coating covering the surface of the magnetic particles. The magnetic particles contain Sm (22.3 mass%), Fe (71.5 mass%), N (3.3 mass%), La (0.48 mass%), W (0.51 mass%) and Ti (0.17 mass%). The coated magnetic powder is obtained by subjecting a magnetic powder containing magnetic particles to a phosphoric acid treatment. In the phosphoric acid treatment in this case, first, after a slurry is obtained by putting the magnetic powder into pure water, a phosphoric acid solution is put into the slurry so that 1 mass% of PO4 of phosphoric acid (H3PO4) is added relative to the solid content of the magnetic particles. Then, the slurry is stirred for 5 minutes, and after solid-liquid separation, vacuum drying is performed at 190°C for 3 hours. Thus, a phosphoric acid coating as a passive film having a PO bond is formed on the surface of the magnetic particles. D with coated magnetic powder 50 is 3.00μm.

[0058] Next, as a modifying material powder, a metal zinc powder containing metal zinc particles (metal zinc purity: 99.9 mass %, D 50 :0.5μm) (modifying material powder preparation step). Next, the coated magnetic powder and the metallic zinc powder are mixed so that the content of the metallic zinc powder becomes 7.5 mass %, and then the coated magnetic powder and the metallic zinc powder are mixed using a vibration mill to obtain a mixed powder (mixing step).

[0059] Next, the mixed powder is compression molded in a magnetic field (magnetic field molding) to obtain a magnetic field molded body (magnetic field molding process). The magnetic field molding is performed in a nitrogen atmosphere, the molding pressure of the magnetic field molding is set to 50 MPa, the application time of the molding pressure of the magnetic field molding is set to 1 minute, and the size of the magnetic field of the magnetic field molding is set to 1600 kA / m. The magnetic field orientation in the magnetic field molding makes the easy magnetization axes of the magnetic particles of the magnetic field molded body consistent.

[0060] Next, the magnetic field formed body is pressure-sintered to obtain a sintered body (pressure sintering process). The pressure sintering is carried out in an argon atmosphere of 97000Pa, the pressure of the pressure sintering (pressing pressure) is set to 900MPa, the temperature of the pressure sintering (pressing temperature) is set to 390°C, and the time of the pressure sintering (pressing time) is set to 24 hours. Through the above process, a rare earth magnet with a sintered body is manufactured. Furthermore, the manufacturing conditions including the composition of the mixed powder and the conditions of the pressure sintering are shown in the following Table 1.

[0061] [Examples 2 to 4 and Comparative Examples 1 to 9]

[0062] The pressure, temperature and time of the pressure sintering are shown in the following Table 1. A rare earth magnet including a sintered body was produced in the same manner as in Example 1 except for this point.

[0063] [Evaluation of Half Width of Diffraction Peak of (024) Plane of Sintered Body]

[0064] X-ray diffraction was performed on the surface perpendicular to the easy magnetization axis of the sintered body of each of Examples 1 to 4 and Comparative Examples 1 to 9, and the X-ray diffraction pattern was measured. The measurement was performed under the conditions of using CuKα radiation in an inert atmosphere. Then, the half-value width [degrees] of the diffraction peak of the (024) plane of the crystal structure of the magnetic phase of the magnetic particles of the sintered body was obtained from the X-ray diffraction pattern. The results are shown in Table 1 below.

[0065] [Evaluation of bulk density]

[0066] The weight and volume of the sintered body of the rare earth magnet of each of Examples 1 to 4 and Comparative Examples 1 to 9 were measured. Then, the bulk density [g / cm 3 ]. The results are shown in the following Table 1.

[0067] [Evaluation of magnetic properties]

[0068] The magnetic properties of the rare earth magnets of Examples 1 to 4 and Comparative Examples 1 to 9 were evaluated. At this time, the rare earth magnets of each example were pulse magnetized at room temperature using a magnetizing magnetic field of 6400 kA / m, and the residual magnetization Br[T] was measured using a VSM (vibrating sample magnetometer) with a maximum magnetic field strength of 1600 kA / m. The results are shown in Table 1 below.

[0069]

[0070] [Investigation]

[0071] As shown in Table 1, in Examples 1 to 4, the pressure (pressing pressure) of the pressure sintering in the manufacturing conditions of the rare earth magnets is 500 MPa or more and 900 MPa or less, the temperature (pressing temperature) of the pressure sintering is 360°C or more and 390°C or less, and the time (pressing time) of the pressure sintering is 1 hour or more and 24 hours or less. As a result, in the evaluation results of the rare earth magnets, the bulk density of the sintered body is 6.2 g / cm 3 As described above, the half width of the diffraction peak of the (024) plane of the crystal structure of the magnetic phase of the sintered body becomes 0.2 degrees or less. As a result, the residual magnetization Br becomes 0.9T or more.

[0072] On the other hand, in Comparative Examples 1 and 2, the half-value width exceeded 0.2 degrees. This is believed to be because the pressure exceeded 900 MPa, which caused the deformation of the magnetic particles to increase and the crystallinity of the magnetic phase to decrease. In Comparative Examples 3 and 4, the bulk density was less than 6.2 g / cm 3 . It is considered that this is because the pressure is less than 500MPa, which makes it impossible to increase the density of the sintered body. In Comparative Example 5, the half-width exceeds 0.2 degrees. It is considered that this is because the temperature exceeds 390°C, causing the deformation of the magnetic particles to increase and the crystallinity of the magnetic phase to decrease. In Comparative Example 6, the half-width exceeds 0.2 degrees. It is considered that this is because the temperature is less than 360°C under the condition of a pressure of 900MPa, causing the hardness of the magnetic particles to be maintained, the squeezing force between the magnetic particles to increase, and as a result, the crystallinity of the magnetic phase to decrease. In Comparative Example 7, the half-width exceeds 0.2 degrees. It is considered that this is because the temperature exceeds 390°C, causing the magnetic powder and the zinc component to over-react, and the strain of the magnetic phase to increase. In Comparative Example 8, the volume density is lower than 6.2g / cm 3 . This is believed to be because the temperature was less than 360°C under a pressure of 500 MPa, which made it impossible to densify the sintered body. In Comparative Example 9, the half-value width exceeded 0.2 degrees. This is believed to be because the deformation of the magnetic particles became larger due to the time exceeding 24 hours, and the crystallinity of the magnetic phase decreased.

[0073] As mentioned above, although embodiment of this invention is described in detail, this invention is not limited to the said embodiment, Various design changes are possible within the range which does not deviate from the spirit of this invention described in a claim.

Claims

1. A method for manufacturing a rare earth magnet, characterized in that: have: A step of preparing a magnetic powder containing Sm, Fe and N; A step of preparing a modifying material powder containing at least one of metallic zinc and a zinc alloy; A step of obtaining a mixed powder by mixing the magnetic powder and the modifying material powder; A step of obtaining a magnetic field molded body by compression molding the mixed powder in a magnetic field; and a step of obtaining a sintered body by pressure-sintering the magnetic field formed body, In the pressure sintering, the magnetic field forming body is pressure sintered at a pressure of 500 MPa to 900 MPa and a temperature of 360° C. to 390° C. for a period of 1 hour to 24 hours.

2. A rare earth magnet, characterized in that: A sintered body comprising a mixed powder, the mixed powder comprising a magnetic powder and a modifying material powder, the magnetic powder containing Sm, Fe and N, the modifying material powder containing at least one of metallic zinc and a zinc alloy, The half-value width of the diffraction peak of the (024) plane of the sintered body measured by X-ray diffraction is 0.2 degrees or less, The bulk density of the sintered body is 6.2 g / cm 3 above.

Citation Information

Patent Citations

  • Rare earth magnet and manufacturing method thereof

    JP2023077289A